INFREQUENT WEIGHTED ITEMSET MINING FOR TRANSACTIONAL DATABASES USING FREQUENT PATTERN GROWTH - Mr. D. H. Dewarde; Assist.Prof. S. A. Kahate (International Journal of Innovations in Engineering Research and Technology, 2021)
Mining Weighted Item sets from a transactional database includes to the discovery of itemsets with high utility like profits.Although a number of relevant techniques have been planned in recent years, they obtain the problem of producing a large number of candidate itemsets for high utility itemsets. Such a large number of candidate itemsets weakens the mining performance in terms of execution time and space requirement. In this paper we have concentrate on UP-Growth and UP-Growth+ algorithmwhich will overcome this impediment. This technique includes tree based data structure finding itemsets, UP-Tree for generating candidate itemsets with two scan of database. In this paper we extend the functionality of UP-Growth and UP-Growth+ algorithms on transactional database. The situation may become poorwhen the database contains lots of long transactions or long high utility itemsets. An appearing topic in the field of data mining is utility mining. The main goal of utility mining is to identify the itemsets with highest utilities, by considering profit, quantity, cost or other user preferences. This topic includes many applications in website click stream analysis, business promotion in chain hypermarkets, cross marketing in retail stores, online e-commerce management, and mobile commerce environment planning and even finding important patterns in biomedical applications.